Human Fire Legacies on Ecological Landscapes - Power, Mitchell J.; Codding, Brian F.; Taylor, Alan H.; Swetnam, Thomas W.; Magargal, Kate E.; Bird, Douglas W.; O’Connell, James F. (Frontiers in Earth Science, 2018)
The primacy of past human activity in triggering change in earth’s ecosystems remains a contested idea. Treating human-environmental dynamics as a dichotomous phenomenon---turning “on” or “off” at some tipping point in the past---misses the broader, longer-term, and varied role humans play in creating lasting ecological legacies. To investigate these more subtle human-environmental dynamics, we propose an interdisciplinary framework, for evaluating past and predicting future landscape change focused on human-fire legacies. Linking theory and methods from behavioral and landscape ecology, we present a coupled framework capable of explaining how and why humans make subsistence decisions and interact with environmental variation through time. We review evidence using this framework that demonstrates how human behavior can influence vegetation cover and continuity, change local disturbance regimes, and create socio-ecological systems that can dampen or even override, the environmental effects of local and regional climate. Our examples emphasize how a long-term interdisciplinary perspective provides new insights for assessing the role of humans in generating persistent landscape legacies that go unrecognized using a simple natural-versus-human driver model of environmental change.